Among the reasons for the importance of sports on holiday - Cenk Temel; Murat Sentuna; Velittin Balcı (Türk Spor ve Egzersiz Dergisi)
The purpose of the study, among the causes of the Turkish people go on holiday is to determine the importance of sports and analyzed according to gender, age, income and education levels the causes of sport participation on holiday. 2.104 people participated in this research (1.274 male60.6% and 830 female 34.4% between the ages of 16-60). In this study, as a means of data collection “The Opinion Survey About Reasons For Doing Sports On Holiday” was used. Of the participants in the study, noted that a total of 1.527 people (936 male 61.2%, 591 female 38.8%) on holiday do sports and 282 participants, into their severity rating ranking, took sports item. In analyzing the data mean, standard deviation, percent, frequency distributions, participants during the holidays as a reason to play sports in the analysis of their answers to the propositions presented, by gender, independent-samples t test and age, education and income levels of the one-way anova analysis were used. Results showed that there are differences according to participants' gender, age, and income and education level. Suggestions presented to the participants “to attend any sporting event as a spectator” 73 people (25.9%) never, “as a participant to participate in any sporting activity” 75 people (26.6%) rarely and “to participate in extreme sports” of 112 people (39.7) always responded. Between men and women, “to find different sports facilities” and “learn a new sport” is a significant difference between the suggestions (p=0.046 and 0.004 lt;0.05) were found. Between 16-25 years and 46-55 years of age (p=0.046 lt;0.05), between 500-1000 TL and 1001-2000 TL (p=0.049 lt;0.05) and 2001 TL and above (p=0.019 lt;0.05) income, between post-graduate education and high school (p=0.02 lt;0.05) and college graduates (p=0.003 lt;0.05)significant differences were found.As a result of these findings, among people who want to do sport on holiday sex, age, income and education levels may be concluded that differ.